التصميم بمساعدة الحاسوب وتحسين أداء خط إنتاج درفلة الحديد على الساخن - حلبي, موريس (Latakia University Journal -Engineering Sciences Series, 2016)
يقدم هذا البحث دراسة هدفها تحسين أداء آلة درفلة الحديد على الساخن , وجعلها مطابقة للمواصفات الدولية حيث تشمل الدراسة مرحلتين: الأولى وتتضمن النمذجة الرياضية ومحاكاة آلة الدرفلة . أما المرحلة الثانية فتشمل تطوير واختبار نظم التحكم البديلة .اختبرت صحة هذا النموذج من خلال تحليل منحنيات الأداء المستخلصة من محاكاتها ومقارنتها مع قيم منحنيات وجداول المحطة الحقيقية المأخوذة من HSRMP وذلك من خلال تضمين هذا النموذج لبارامترات النظام المميزة والمتغيرات الممثلة للأداء الحقيقي للمحطة , هذا يجعل منه أداة مفيدة تتيح محاكاة أداء المحطة , تفسير سلوك المتغيرات واختبار الحالات إضافة إلى إمكانية تغير العمل واستراتيجيات التشغيل لتحسين التشغيل بشكل عام . من هذا النموذج أنجز التحليل المبدئي والذي أثبت إمكانية تحسين أداء المحطة بتنفيذ التعديلات التالية :• تقليل قيمة الثابت التكاملي للنماذج المرتبطة بالحلقات المتوضعة في المرحلة الأخيرة• توحيد كل نسب التغذية الردية للحلقات Fed back . • نقل الدائر ليتوضع في المرحلة الأخيرة . ملاحظة : ان الرمز HSRMP هو اختصار للعبارة Hot Strip Rolling Mill Plant وتعني معمل درفلة الحديد على الساخن .This paper presents a study aimed at improving the performance of the machine, hot steel rolling, and make them conform to international standards, where the study includes two phases: the first includes mathematical modeling and simulation programming language with a rolling machine. The second phase will include the development and testing of alternative control systems.I tested the validity of this model through analyzes of performance curves derived from simulated and compared with the values of the curves and tables station real taken from the HSRMP. Through ensure this form to the parameters of the system characteristic variables representing the performance of the real station, this makes it a useful tool allows simulation of plant performance, explain the behavior of variables The test cases in addition to the possibility of change work and operating strategies to improve the overall operation. From this model performed the initial analysis, which proved the possibility of improving the performance of the station to implement the following modifications:• Reduce the value of hard integrative models associated with the rings are positioned in the final stage.• unification of all evil ratios for nutrition workshops. • Revolving transfer is located in the last phase .Note: HSRMP ( Hot strip rolling Mill plant ) .